Ideological Aspects of Public Sector reform: Comparing British Central Government Reforms Under the Premierships of Thatcher, Major, and Blair. - Koskelin, Antti (My University, 2007)
The aim of the study was to find out, what has changed and what has remained the same when comparing the reforms of British central administration during the terms of Margaret Thatcher, John Major, and Tony Blair. The interest in this study lies in the filtration of political ideologies into the reform agendas of the three different Premiers. The starting point of this cross-time comparison is the election of Margaret Thatcher into office in 1979, and comparison is carried into present day. The idea of my study is to see how changes in the public sector are fuelled by political action, using the reforms of administration as the data to be analysed. For this purpose choosing the Thatcher era as starting point was useful, because, in addition to her personality, the global change of ideologies from welfare to neo-liberalism gained momentum. This study consists of a twofold approach to the research questions. The broader question consists of the Premiers and their style of governing, policies, and reforming the administration. The question is formulated as: What kind of ideologies do the Prime Ministers carry into their reforms of central administration in Britain and what kind of reform efforts are there to be seen? A more specific question is: What specific features of the welfare state ideal type and/or the neo-liberal ideal type are present in these reforms chosen and towards which type do they lean the more to? The theory of the study is constructed from a set of theories from different sciences. There are aspects from the theory of public administration, political science, economics, and sociology. The use of different theories leads to the creation of two opposing ideal types of organising state functions on ideological grounds. The first one is the classical welfare state ideal type, and the second one is the market or neo-liberal ideal type, where the role of the state is minimised and society is hierarchical rather than equal. These ideal types are used to compare the reforms of each premier with the help of a deducted, simplified analysis tool. The method of the study is an illustrative cross-time comparison, and a context comparison of three phenomena. As the focus of the study is on the ideological side of public sector reform processes, the selection of the research data reflects that. The main data to be analysed are three reform agendas, or intentional pamphlets, one by each Premier. The agendas are divided into theme pairs according to the analysis tool, and conclusions and results are drawn from the comparison of themes. The main findings were that the reform efforts of Margaret Thatcher were, as expected, almost a prototype of the neo-liberal ideal type. John Major, again as expected, followed the same path, albeit with some differences. In some aspects, he seemed even a harsher opponent of the welfare state ideal type, but in some others, he seemed rather lenient and even protective of the welfare state. Tony Blair was expected not to be very different from his two predecessors. But my findings suggest that there were quite a few differences, as well as quite a few similarities. Partly the problems of analysing Blair’s intentions rose from the bow-to-all-directions nature of his rhetoric. Blair and his New Labour are neither pure neo-liberals nor pure socialists, but somewhat of a centre-of-politics hybrid of the two.
Keywords: Public Sector Reform; Ideology; Great Britain; Thatcher; Major; Blair; fi=Hallintotiede : julkisjohtamisen ohjelma|